Organising cyber security in Australia and beyond. - Smith, Frank; Ingram, Graham (Australian Journal of International Affairs, 2017)
The Internet is an interconnected network and cyber security requires collective action. How that action is organised has important implications for national security, including the defence against cyber attacks and malicious activities. This article explains the origins and institutionalisation of cyber security in Australia--particularly 'civilian cyber security'. The authors trace the origin of Australia's first computer emergency response team and explain how this organisational form spread from the USA. Through it, Australia helped enable international cooperation. Domestically, however, the authors argue that the Australian government has struggled with the delegation, orchestration and abdication of responsibility for civilian cyber security, underinvesting in civilian organisations while overrelying on military and intelligence agencies. The history of this organisational field provides valuable insight into how to improve national policy and operations for cyber security.